Comparative analysis of resected prostate weight in diabetic and non-diabetic benign prostatic hyperplasia patients - Emadouddin Moudi; Abazar Akbarzadeh-Pasha (Babol University of Medical Sciences, 2017)
Background: Benign prostatic hyperplasia (BPH) is the most common benign tumor in men. The etiology of BPH is still unresolved and multiple systems are likely to be involved. The effects of diabetes on urinary system are a risk factor for BPH. We then assessed the effects of diabetes on the parameters related to BPH, especially weight and volume. Methods: This study was conducted on patients with BPH who underwent surgery during 2010-2013. The patients’ demographic and clinical data including age, height, weight, history of diabetes, abdominal sonography, prostate-specific antigen(PSA), fasting blood sugar (FBS), triglyceride, and cholesterol, resected sample weight, and pathological diagnosis were extracted. Results: The mean age of all 225 patients (35 (15.6%) diabetic patients and 190 (84.4%) non-diabetic patients) who entered the study was 71.5±8.7 years. The patients were divided in to 3 body mass index (BMI) groups: 48 (21.3%) were normal, 151 (67.1%) were overweight and 26 (11.6%) were obese. The mean weight of resected prostate was higher in diabetic patients (22.9±6.9 vs 21.7±14.3, P=0.02). The resected prostate weight had a significant relationship with BMI (P=0.001), prostate–specific antigen (PSA) level (P=0.001), and prostate volume sonography (P=0.001). No significant relationship was detected between resected prostate weight with age, FBS and triglyceride however, it is significant with cholesterol. Conclusion: We concluded that diabetes has a role in the development and progression of BPH with effect on prostate weight and volume. As well, BMI is a risk factor in BPH progression.